Language unawareness and reflections of psychological dimensions - Salih, Tara; Brzo, Omed (Humanities Journal of University of Zakho, 2022)
Linguists and researches have clarified that psychology has a deep-rooted relationship with several other scientific fields, sometimes even complementary to each other, for example, psychology and sociology, the social sciences, including economics and politics. All these can display a shade of psychology and psychological implication, especially when trying to detect the factors and motives of the human behavior. Due to such practical closeness between psychology and sociology, both mentioned fields of knowledge examine and scrutinize human language and behavior. The present study discusses the social psychology of the individual where individual environment impacts the social systems of language, laws, norms, religions and the individual mindset, hence shaping the psychological being of the individual. What is the relationship between language unawareness and the reaction of psychological dimensions in any situation: during peace, revolutions, and national disasters? This study is entitled “Language Unawareness and Reflections of Psychological Dimensions”. It comprises two sections: an introduction, a conclusion, and also a list of references. Besides, the abstract of the study has been translated into both English and Arabic.